The Effect of Ginger on Nausea and Vomiting in Pregnant Women - Irawan, Dea Fitria; Dewi, Sentya Kurnia; Irmayanti, Putri Adinda; Wijayanti, Wijayanti; Fiany, Alce; Gusriani, Gusriani; S, Teresia; Padlillah, Rahmi; Retnowati, Yuni (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2024)
Nausea and vomiting are common problems experienced by pregnant women, especially during the first trimester of pregnancy. Ginger has been the focus of research in efforts to treat these symptoms. This study aims to determine the effectiveness of ginger in treating nausea and vomiting in first trimester mothers. This research method is systematic (systematic review) which is a scientific approach used to integrate and compile findings from various relevant studies in one comprehensive analysis. Researchers conducted a very thorough and structured search in various literature sources to find studies that were relevant to the research question. The research results show that giving ginger regularly for 4 days can reduce the frequency of nausea and vomiting in pregnant women who experience hyperemesis gravidarum. Giving ginger to pregnant women in the first trimester can cause side effects such as stomach irritation, dry mouth and diarrhea. Apart from that, giving ginger in high doses can also cause an increased risk of bleeding and uterine contractions. Ginger has the potential to reduce nausea and vomiting and their intensity, and may also influence the duration of symptoms of nausea and vomiting in pregnant women, especially during the first trimester of pregnancy.